2022
DOI: 10.1590/0034-7167-2021-0554
|View full text |Cite
|
Sign up to set email alerts
|

Online mental health care during the COVID-19 pandemic

Abstract: Objective: Identify users, services, and reasons for seeking online mental health care during the COVID-19 pandemic. Methods: A descriptive, retrospective study, with documentary analysis of medical records of users served between April and July 2020. Results: Of the 258 accesses, 159 were complete, and 99 were offline messages. Although there were 61 (38.36%) consultations in May, in April, there were 49 (30.82%) in 18 days of reception. More than 89% of accesses were women between 40 and 59 years. Among th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
1
0
2
Order By: Relevance
“…In addition to the psychosocial repercussions involved in the work dimension, the study also showed that there are social repercussions arising from the installed social insecurity, such as exposure to political conflicts associated with crises in the government, dissemination of false information, and formulation of Conspiracy theories, exposing men to forces contrary to those aimed at preventive care ( Bilewicz et al, 2019 ; Guedes et al, 2021 ; The Lancet , 2020 ).…”
Section: Discussionmentioning
confidence: 94%
“…In addition to the psychosocial repercussions involved in the work dimension, the study also showed that there are social repercussions arising from the installed social insecurity, such as exposure to political conflicts associated with crises in the government, dissemination of false information, and formulation of Conspiracy theories, exposing men to forces contrary to those aimed at preventive care ( Bilewicz et al, 2019 ; Guedes et al, 2021 ; The Lancet , 2020 ).…”
Section: Discussionmentioning
confidence: 94%
“…Para Guedes et al (2021), o cuidado em saúde mental é essencial no que diz respeito a estratégias para a promoção da saúde. Portanto, destacam a escuta terapêutica como um importante aliado nesse cuidado, pois se encontra como instrumento de acolhimento, cuidado e intervenção, sendo um meio de suporte à saúde mental em tempos de pandemia.…”
Section: Contribuições Para Reduzir Os Impactos Na Saúde Men-tal Dos ...unclassified
“…O destaque foi para a condição de ser mulher e de fazer escala laboral de 12 ou 24 horas como fatores de risco para esses transtornos mentais, somados à preocupação com a infecção de um membro da família12 .Os resultados encontrados na análise da ideação de suicídio na vida (OR = 2,36; IC95% 1,63;3,42) e no último mês (OR = 4,13; IC95% 2,01;8,46) entre os nutricionistas indicam a necessidade de se aprimorar a atenção à saúde mental desse profissional e de se promoverem ações de respostas às suas consequências. Estudo brasileiro que avaliou as motivações para busca de atendimento on-line em saúde mental durante a pandemia da COVID-19 identificou que mais de 89% dos acessos foram realizados por mulheres com idade compreendida entre 40 e 59 anos e que dentre tais motivações destacaram-se ansiedade, depressão e ideação suicida26 .Aspectos relacionados ao estilo de vida estiveram associados à ideação suicida em pesquisa feita com mulheres no Piauí, cuja coleta de dados ocorreu entre agosto de 2015 e março de 2016. Evidenciou-se que aquelas que eram possíveis dependentes de álcool (OR = 3,9 IC95% 1,96;8,15) e de tabaco (OR = 3,3; IC95%1,46;6,72) tinham mais chances de possuir ideação suicida27 .…”
unclassified